Impact of Household Cooking Techniques on African Nightshade and Chinese Cabbage on Phenolic Compounds, Antinutrients, in vitro Antioxidant, and β-Glucosidase Activity - Managa, Millicent G.; Shai, Jerry; Thi Phan, Anh Dao; Sultanbawa, Yasmina; Sivakumar, Dharini (Frontiers in Nutrition, 2020)
Different household cooking techniques (boiling, steaming, stir-frying, and microwave) were tested on the changes of targeted phenolic compounds, antioxidant property (FRAP activity), α-glucosidase activity, antinutritive compounds and sensory properties in commonly consumed traditional leafy vegetables in Southern Africa, the non-heading Chinese cabbage (Brassica rapa L. subsp. chinensis) and African nightshade (Solanum retroflexum Dun). Stir-frying increased the kaempferol glycosides, sinapoyl malate, rutin and isorhamnetin-O-hexoside, in Chinese cabbage leaves, followed by steaming. Similarly, stir-frying increased kaempferol-3-O-rutinoside, kaempferol-O-rhamnosyl-hexoside, kaempferol-3-O-sinapoyldihexoside-hexoside rutin, neochlorogenic, chlorogenic, caffeoylmalic acids and quercetin-3-O-xylosyl-rutinoside in nightshade leaves, followed by steaming. Biomarkers, sinapoyl malate (Chinese cabbage) and caffeoylmalic acid (nightshade) separated the stir-frying from the other cooking techniques. Steaming and stir-frying techniques significantly increased the FRAP activity and boiling and microwaving reduced the tannin, oxalate, and phytate contents in both leafy vegetables and steroidal saponins in nightshade. Extracts (at the concentrations 50 and 6.25 mg mL-1) from the stir-fried and steamed leaves of Chinese cabbage and nightshade demonstrated the highest inhibitory effect (>75%) against α-glucosidase activity. Panelists preferred the stir-fried Chinese cabbage and nightshade leaves, followed by steaming.